Discovery and characterisation of terpenoid biosynthesis enzymes from Daphniphyllum macropodum - Kaouthar Eljounaidi; Caragh B. Whitehead; Emily Radley; Marissa H. Petrou; Katherine Newling; Sally James; Benjamin R. Lichman (BMC Plant Biology)
Abstract Terpene synthase (TPS) enzymes are known to be pivotal in the biosynthesis of terpenoids in plants and microbes. These enzymes catalyse the transformation of ubiquitous acyclic prenyl diphosphate substrates into diverse hydrocarbon skeletons. Mining TPS genes from the genomes and transcriptomes of diverse taxa of plants and microbes is a powerful tool for the discovery of new enzymes and new chemistries. In this work, we used a combination of long-read and short-read RNA sequencing technologies to develop a high-quality transcriptomic data set for Daphniphyllum macropodum, a poorly studied plant rich in unique terpene derived metabolites. Through mining the transcriptome, we identified different terpene-related enzymes, including prenyl transferases (PTs), triterpene cyclases (TTCs), and terpene synthases (TPSs). These were expressed in a Nicotiana benthamiana system together with rate-limiting enzymes HMGR or DXS to boost the metabolic flux. The products were then analysed using GC-MS. We have identified four monoterpene synthases producing diverse linear, monocyclic and bicyclic monoterpenes including linalool, limonene, geraniol, and pinene. We also identified four sesquiterpene synthases, one producing caryophyllene, one α-guaiene, and two producing a blend of sesquiterpenes. In addition, we demonstrated the activity of two triterpene cyclases both forming cycloartenol, as well as a geranylgeranyl diphosphate synthase (GGPP synthase). Together, these findings expand the known chemical space of D. macropodum terpenoid metabolism and enable further investigations of terpenoids in this under-explored plant species.